Dampak Komunikasi, Kerjasama Tim dan Kedisiplinan Terhadap Kinerja Karyawan pada PT. UMB (BOGA) di Yogyakarta - Ichsan Nurrozi; Subarjo Subarjo (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the impact of communication, teamwork, and discipline on employee performance at PT UMB (BOGA) in Yogyakarta. This research method is purposive sampling or data collection based on certain criteria. The results showed that partially communication, discipline had a significant positive effect on the performance of PT UMB (BOGA) employees in Yogyakarta. And teamwork has no effect on the performance of PT UMB (BOGA) employees in Yogyakarta. Conclusions, communication, teamwork, discipline simultaneously have a significant effect and have an influence of 52.5% on employee performance at PT UMB (BOGA) in Yogyakarta, while 47.5% of other variables are not present in this study. Keywords: Communication, Teamwork, Discipline, Employee Performance.